Peran Kepemimpinan Tokoh Informal terhadap Kemandirian Pemuda Sekitar Hutan di Kabupaten Bogor - Yoyon Haryanto; Suyadi (Jurnal Pemberdayaan Masyarakat, 2021)
Youth around the forest in general is still very trusting, submissive and obedient to their informal leader. Independence of youth around the forest can be measured from the power strain, competitiveness and sanding. The purpose of this study was to analyze the factors that influence the leadership role of informal leaders, youth independence around the forest, and the leadership role of informal leaders on youth independence around the forest. The research was conducted from October to November 2020, located in the village of Pasir Madang, Sukajaya Subdistrict, Bogor Regency with a sample size of 50 youth. Data were analyzed using path analysis (path analysys). The results of this study are the factors that directly affect the leadership role of informal figures are the individual factors of informal figures, the independence factor of youth around the forest is influenced by the leadership role of informal figures and individual factors of informal figures, and the leadership role of informal figures significantly affects the independence of youth around the forest. Extension support by the government tarhadap informal leaders need to be improved, so that the informal leaders can be more active, innovative, and also care about the community